The Cape genus Micranthus (Iridaceae: Crocoideae), nomenclature and taxonomy - P. Goldblatt; J. C. Manning; R. E. Gereau (Bothalia: African Biodiversity & Conservation, 2013)
The genus Micranthus (Pers.) Eckl., has traditionally been treated as comprising three species, all with virtually identical, bilaterally symmetric, deep or pale blue to white flowers arranged in crowded, 2-ranked spikes and with divided style branches, but differing in their foliage. Examination of plants in the field and herbarium shows that there are four additional species. M. filifolius Goldblatt & J.C.Manning, from the Caledon District of the southwestern Western Cape, has up to six, filiform leaves, the blades of at least the lowermost terete and cross-shaped in section, and usually pale blue-mauve flowers. M. simplex Goldblatt & J.C.Manning from high elevations on Zebrakop, Piketberg, has the smallest flowers in the genus, white but tinged lilac as they age, linear leaves up to 1.5 mm wide, and undivided style branches. M. cruciatus Goldblatt & J.C.Manning, from the northern Cedarberg and Bokkeveld Mtns, has up to four leaves, the lower with linear or terete blades with heavily thickened margins and central vein and relatively large flowers, unusual in having the style dividing at the mouth of the perianth tube into particularly long branches, these deeply divided as is typical of the genus. M. thereianthoides Goldblatt & J.C.Manning, from the Paardeberg south of Malmesbury, is unique in the genus in having flowers with an elongate perianth tube. We also document the occurrence of large populations of putative hybrids at some sites. We provide a complete revision of Micranthus with original observations on leaf anatomy, pollen morphology and reproductive biology and discuss its confused taxonomic and nomenclatural history and that of the three common species of the genus, known for over 150 years. In so doing, we neotypify Gladiolus alopecuroides L. (1756) [= Micranthus alopecuroides (L.) Eckl. (1827)], type of the genus, and choose lectotypes for M. plantagineus Eckl. var. junceus Baker (1892) and Gladiolus fistulosus Jacq. Now with seven species, Micranthus remains endemic to the Cape flora region, extending from its extreme northern limit in the Bokkeveld Mtns south-eastwards to Port Elizabeth. We also deal with the genera Paulomagnusia Kuntze and Beilia Kuntze with which Micranthus has sometimes been associated, although both are nomenclatural synonyms of Thereianthus G.J.Lewis, a genus close allied to Micranthus.